Use of antibodies neutralizing epithelial cell infection to diagnose patients at risk for CMV Disease after transplantation. Issue 5 (May 2016) - Blanco-Lobo, P.; Cordero, E.; Martín-Gandul, C.; Gentil, M.A.; Suárez-Artacho, G.; Sobrino, M.; Aznar, J.; Pérez-Romero, P.
Summary: Objectives: Although a CMV-specific T-cell response is associated with reduced risk for infection after transplantation, some patients still develop CMV disease. Thus, the characterization of additional parameters of the CMV-specific immune response that correlate with the control of CMV infection and disease and their use in defining thresholds that can be applied to clinical practice is of interest. Methods: In a cohort of high risk solid organ transplant recipients we characterized CMV-specific T-cell responses using intracellular cytokine staining upon stimulation with pp65 and IE-1 peptides, and levels of CMV-specific antibodies neutralizing infection in fibroblast (MRC-5) and epithelial (ARPE-19) cells using microneutralization assays. Results: Although patients with a positive (≥0.25%CD8 + CD69 + IFN-γ+) T-cell response were 6.4 fold more protected (OR 6.4, 95% CI 1.6–25.3; p < 0.001) from CMV infection than patients without a response, 2 (4.2%) patients developed disease. We defined a cut-off titer for epithelial cell neutralizing antibodies of ≥480 that correlated with disease protection. Thus, patients with a CMV-specific T-cell response and titers ≥480 were 14.2 fold more protected from CMV infection (OR 14.2, 95% CI 5–40.2; p < 0.001) and had no episodes of CMV disease. Conclusions: Our results indicate that antibodies neutralizing epithelial cell infection may have an important role in long-term protection. Quantification of antibodies neutralizing epithelial cells, in addition to the T-cell response, may be useful for identifying patients with lower risk for CMV disease.